Buku Wisata Kalimantan Barat untuk Mendukung Kegiatan Membaca Ekstensif Bahasa Inggris di Universitas Tanjungpura - Ikhsanudin Ikhsanudin; Suparjan Suparjan (ICoTE Proceedings, 2018)
This article argues the importance of designing tourism book of Kalimantan Barat to support extensive reading activities in Universitas Tanjungpura, Pontianak-Indonesia. Amid the vast development of educational and information technology and creative change of learning strategies, more materials that are presented in creative ways are required to support learning in universities. Based on a critical investigation on five aspects, the writers concluded that books on local tourism, particularly in the scope of Kalimantan Barat (West Kalimantan or West Borneo), are required to support students’ extensive reading activities in Universitas Tanjungpura. The five factors cover the significance, the extensive reading theory, the language teaching materials theory, the gaps between needs and availability (supplies), and the potential contribution to the university’s vision accomplishment.